Analisis Mitigasi Risiko Akad Murābaḥah pada Pembiayaan Cicil Emas di Bank Syariah Indonesia KCP Pamekasan Jokotole - Arifin, Muhamad; Farisul Haq (Dirosah Islamiyah, 2026)
Abstracts This research is motivated by the importance of implementing appropriate risk mitigation in banking financing products to avoid losses, as successfully applied to the gold installment financing product at Bank Syariah Indonesia (BSI) KCP Pamekasan Jokotole. The purpose of this study is to determine the mechanism of the murābaḥah contract and to analyze the risk mitigation applied to gold installment financing at the bank. This field research utilizes a qualitative approach, with data collection methods consisting of observation, interviews, and documentation involving employees and customers as the research subjects. The validity of the data was tested using the source triangulation technique. The results show that: 1) The gold installment financing mechanism begins with customer consultation, gold selection, ordering from PT Antam, signing forms and the murābaḥah contract, paying a 20% down payment, and disbursing 80% of the financing into BSI net banking to be transferred to PT Antam, ending with the customer receiving the Gold Ownership Certificate (SBKE). 2) Potential risks include credit risk, market risk, and operational risk. The mitigation steps taken by BSI KCP Pamekasan Jokotole to manage market risk involve setting a 20% down payment to anticipate gold price fluctuations. Operational risk mitigation is carried out through regular internal supervision, while credit risk mitigation is implemented through BI Checking (credit history checks), customer education, and the strict application of the 5Cs of credit analysis.